2000
DOI: 10.1046/j.1365-2044.2000.055002131.x
|View full text |Cite|
|
Sign up to set email alerts
|

THIS ARTICLE HAS BEEN RETRACTED Acute phase response to nitroprusside‐induced controlled hypotension in patients undergoing radical prostatectomy

Abstract: SummaryThis study evaluated the effects of sodium nitroprusside-induced controlled hypotension on the acute phase response in patients undergoing radical prostatectomy. Thirty patients were randomly allocated to two groups, a hypotension group (mean arterial blood pressure was adjusted to 50 mmHg) and a control group (mean arterial blood pressure > 70 mmHg). C-reactive protein increased signi®cantly in the hypotension group from 0.13 (0.23) to 9.85 (2.84) mg.ml À1 and in the control group from 0.15 (0.27) to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
1
3
0
1
Order By: Relevance
“…Although this finding is similar to other recent publications of deliberate hypotension, [6][7][8] it is clear that a zero numerator (no SAEs in a study population) does not imply zero risk. In this study population the risk of an SAEs was less than 3%.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although this finding is similar to other recent publications of deliberate hypotension, [6][7][8] it is clear that a zero numerator (no SAEs in a study population) does not imply zero risk. In this study population the risk of an SAEs was less than 3%.…”
Section: Discussionsupporting
confidence: 91%
“…25 There is evidence that nitroprusside-induced hypotension is associated with a significant increase in acute phase proteins. 7 This finding may indicate transient gut ischemia secondary to hypotension, although a further study of patients undergoing maxillo-facial surgery (with controlled hypotension using isoflurane or esmolol/nitroglycerin), found that gastric intramucosal pH values remained above 7.37 leading to the conclusion that splanchnic perfusion was not compromised. 8 Overall, these findings suggest that deliberate hypotension may be applied to patients who are carefully selected, based on appropriate exclusion criteria.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Weiterhin wird das Verfahren eingesetzt, um ein weitgehend blutleeres Operationsfeld zu schaffen, dem Operateur damit das Vorgehen zu erleichtern (z. Bisher publizierte Untersuchungen [2,5,8,9,10,11] zeigen auf, dass selbst mit einer Absenkung des MAP auf etwa 50 mmHg nicht alle Patienten mit einer nennenswerten Verminderung des intraoperativen Blutverlusts im Vergleich zu "normotensiven Patienten" reagieren, Bei der Ausschaltung intrakranieller Aneurysmen soll durch die Anwendung der "kontrollierten Hypotension" die Wandspannung im Aneurysma herabgesetzt und damit die Rupturgefahr vermindert werden.…”
Section: Ziele Verfahren Und Mechanismen Der "Kontrollierten Hypotenunclassified
“…Sodium nitroprusside (SNP) 6,16 and nitroglycerin (NTG) 5,17 are often used for hypotensive anaesthesia because they are potent vasodilators with predictable, short-acting and easily reversible effects. A significant reduction in blood loss 20 and an improvement in the quality of the surgical field 18 have been achieved with controlled hypotensive anaesthesia induced using SNP or NTG.…”
mentioning
confidence: 99%